2002
DOI: 10.1007/s00221-001-0988-2
|View full text |Cite
|
Sign up to set email alerts
|

Two phases of intracortical inhibition revealed by transcranial magnetic threshold tracking

Abstract: Intracortical inhibition was investigated in normal human volunteers by paired-pulse transcranial magnetic stimulation, using a new, computer-assisted threshold-tracking method. Motor threshold was defined as the stimulus amplitude required to evoke a motor evoked potential of 0.2 mV (peak-to-peak) in abductor pollicis brevis, and inhibition was measured as the percentage increase in threshold, when the test stimulus was preceded by a subthreshold conditioning stimulus. This method was used to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
340
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(359 citation statements)
references
References 22 publications
18
340
0
1
Order By: Relevance
“…This information can be used to facilitate comparisons between studies. For example it confirms that when performing a SICI protocol, using an intensity of stimulation (for the conditioning stimulus) of 100% of the aMT (Di Lazzaro et al, 2006;Orth et al, 2003) or of 80 % of rMT (Fisher et al, 2002;Maeda et al, 2002) should yield similar results.…”
Section: Comparisons Of Tms Measures Between Resting and Active Condisupporting
confidence: 58%
See 2 more Smart Citations
“…This information can be used to facilitate comparisons between studies. For example it confirms that when performing a SICI protocol, using an intensity of stimulation (for the conditioning stimulus) of 100% of the aMT (Di Lazzaro et al, 2006;Orth et al, 2003) or of 80 % of rMT (Fisher et al, 2002;Maeda et al, 2002) should yield similar results.…”
Section: Comparisons Of Tms Measures Between Resting and Active Condisupporting
confidence: 58%
“…Lack of difference between the SICI measured at rest and during active conditions is somewhat surprising given that some authors have reported decreased inhibition under active conditions compared to resting conditions (Fisher et al, 2002;Ridding et al, 1995). However, the effect of muscle contractions on intracortical inhibition has been shown to vary according to the intensity of muscle contractions (SICI decreases as the muscle contractions increase, and a low contraction level (7.5±2.5% of MVC) was used in the present study), to the intensity of the conditioning stimulus as well as to the intensity of the test stimulus (Ortu et al, 2008;Roshan et al 2003).…”
Section: Mep Amplitudementioning
confidence: 94%
See 1 more Smart Citation
“…The test stimulus (TS) was adjusted to produce an MEP of ϳ1 mV at rest. TS was delivered 2.5 ms after CS, an optimal interstimulus interval for eliciting SICI and to avoid mixture of the two phases of inhibition (Fisher et al, 2002). Fifteen TS and CS were pre- sented randomly at each time interval, and responses were recorded for off-line analysis.…”
Section: Methodsmentioning
confidence: 99%
“…ISI of 1 millisecond was also tested because the underlying mechanisms for SICI at 1 millisecond may be different from those at other ISIs. 15,16 Intracortical facilitation (ICF) represents a facilitatory process that a subthreshold S1 facilitates the response to a subsequent superthreshold S2 at ISIs of 6 to 30 milliseconds. 2 We tested ICF with ISIs of 10 and 15 milliseconds.…”
mentioning
confidence: 99%